2011
DOI: 10.4067/s0718-58392011000100018
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Nitrate Leaching in Irrigated Wheat with Different Nitrogen Fertilization Strategies in an Alfisol

Abstract: Consumption of water contaminated with nitrates is associated with important health effects such as methemoglobinemia and gastric cancer. Intensive agriculture, which uses large quantities of N fertilizer, is the main source of nitrates in water systems. There are several strategies to reduce leaching and increase Nitrogen Use Efficiency (NUE). An experiment was conducted with spring wheat (Triticum aestivum L.) under sprinkler irrigation (center pivot) to determine if adjusted N applications using precision a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…However, were considerably higher than those obtained by Salazar et al (2010) in other Andisol (< 4.2 kg N ha -1 ) with 400 kg N ha -1 added as slurry and artificial fertilizers, mainly explained by gaseous losses and soil matrix retention. Claret et al (2011) in an Alfisol under 1400 mm of rainfall, reported NL values < 7.9 kg N ha -1 but without significant differences between fertilized and control soils. In central Chile, Iriarte (2007) reported risks of NL in 27% of soils (Mollisols, Inceptisols, and Alfisols) and 63% of drinking water samples analyzed showed nitrate concentrations above the threshold prescribed by the INN (1984) of 10 mg L -1 .…”
Section: Water Budget and Nitrate Leachingmentioning
confidence: 91%
“…However, were considerably higher than those obtained by Salazar et al (2010) in other Andisol (< 4.2 kg N ha -1 ) with 400 kg N ha -1 added as slurry and artificial fertilizers, mainly explained by gaseous losses and soil matrix retention. Claret et al (2011) in an Alfisol under 1400 mm of rainfall, reported NL values < 7.9 kg N ha -1 but without significant differences between fertilized and control soils. In central Chile, Iriarte (2007) reported risks of NL in 27% of soils (Mollisols, Inceptisols, and Alfisols) and 63% of drinking water samples analyzed showed nitrate concentrations above the threshold prescribed by the INN (1984) of 10 mg L -1 .…”
Section: Water Budget and Nitrate Leachingmentioning
confidence: 91%
“…This is due to the slow release of N that sometimes does not coincide with the stages of higher N uptake by the crops, increasing leaching (Kirchmann and Bergström, 2001). Research on fertilization management to reduce leaching is very limited in Chile, and it is also focused on industrial crops (Claret et al, 2011;Salazar et al, 2019). This suggests the need for further research by extending studies to the important vegetables consumed in the country.…”
Section: Introductionmentioning
confidence: 99%
“…One of the new directions in this area is the use of binary regression [4,5]. More studied areas include geostatistics, which allows mapping the nutrient content in the soil and other indicators for optimal farm management [6][7][8]. It should be noted that the ordinary kriging method is traditionally used from geostatistical tools to predict the spatial distribution of various agro-ecological indicators [9][10][11].…”
Section: Introductionmentioning
confidence: 99%